Fragments in philosophy and science;: being collected essays and addresses - Baldwin, James Mark (C. Scribner's Sons, 1902)
Philosophy: its relation to life and education.--The ideslism of Spinoza.--Recent discussion in materialism.--Professor Watson on reality and time.--The cosmic and the moral.--Psychology past and present.--The postulates of physiological psychology.--The origin of volition in childhood.--Imitation: a chapter in the natural history of consciousness.--The origin of emotional expression.--The perception of external reality.--Feeling, belief, and judgment.--Memory for square size.--The effect of size-contrast upon judgments of position in the retinal field.--An optical illusion.--New questions in mental chronometry. Types of reaction.--The "type-theory" of reaction.--The psychology of religion.--Shorter philosophical papers.--Shorter literary papers.